Specialized Training In Nursing Education: A Scoping Review Of Implications For Quality Of Care - Sudrajat, Diwa Agus; Kumala, Tria Firza (Medical-Surgical Journal of Nursing Research, 2025)
Background: Healthcare malpractice remains a critical issue that threatens patient safety and undermines public trust in health systems, particularly within nursing practice. Increasing clinical complexity, ethical challenges, and technological integration have intensified the need for well-prepared nurses. Consequently, nursing education must incorporate effective training strategies to reduce malpractice risk and enhance safe care delivery. Objective: This scoping review aimed to map and synthesize existing evidence on educational strategies for malpractice prevention in nursing education. Methods: The review was conducted following the Joanna Briggs Institute methodology and the PRISMA-ScR reporting guidelines. A comprehensive literature search was performed using PubMed, CINAHL, ERIC, and Google Scholar, covering publications from 2015 to 2025. Eligible studies focused on nursing education, malpractice prevention, and specialized or innovative training approaches. Data were systematically extracted, appraised using established tools, and analyzed through thematic synthesis. Results: Fifteen studies met the inclusion criteria. The findings identified diverse educational strategies, including simulation-based learning, gamification, case-based discussions, and digital health technologies. These approaches were associated with improved clinical competence, ethical judgment, and student engagement. However, variability in training duration and limited long-term outcome evaluation were noted across studies. Conclusion: Specialized, evidence-based training within nursing education is essential for reducing malpractice risk and strengthening patient safety. Strategic integration of innovative methods, combined with sustained evaluation, may enhance nurses’ preparedness to address ethical and legal challenges in clinical practice